2004
DOI: 10.4319/lo.2004.49.5.1722
|View full text |Cite
|
Sign up to set email alerts
|

Neither with nor without you: A complex algal control on bacterioplankton in a high mountain lake

Abstract: The literature proposes that the microbial loop is a key link for ecosystem functioning, particularly in oligotrophic conditions. From original and published data for a period spanning 1986 to 1999, we examined the food web structure of a clear-water, oligotrophic, high mountain lake. The heterotrophic microbial food web was weakly developed in a grazing food chain dominated by copepods and phytoplankton, the latter mainly composed of mixotrophic flagellates. Bacteria constituted a minor component of the plank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 66 publications
8
75
0
Order By: Relevance
“…However, increasing evidence from natural environments suggests that pigmented nanoflagellates (PNF) can also contribute greatly to bacterivory at certain times or at certain depths within the water column (Bird & Kalff 1986, Sanders et al 1989, Berninger et al 1992, Hall et al 1993, Safi & Hall 1999, Hitchman & Jones 2000, Medina-Sánchez et al 2004, Unrein et al 2007). For example, reported that the PNF were responsible for 86% of the entire nanoflagellate bacterivory in the upper layer of the Bay of Aarhus, but accounted for only 19% below the pycnocline.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence from natural environments suggests that pigmented nanoflagellates (PNF) can also contribute greatly to bacterivory at certain times or at certain depths within the water column (Bird & Kalff 1986, Sanders et al 1989, Berninger et al 1992, Hall et al 1993, Safi & Hall 1999, Hitchman & Jones 2000, Medina-Sánchez et al 2004, Unrein et al 2007). For example, reported that the PNF were responsible for 86% of the entire nanoflagellate bacterivory in the upper layer of the Bay of Aarhus, but accounted for only 19% below the pycnocline.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet radiation (UVR) is a major worldwide stressor with farreaching implications for ecological interactions and an overall negative effect on the survival and growth of organisms (Bancroft et al 2007;Hä der et al 2007). However, few studies have reported the effects of the interaction between global stressors, such as UVR and nutrient inputs, on trophic interactions (Medina-Sá nchez et al 2006).…”
mentioning
confidence: 99%
“…Berninger et al (1992) showed that mixotrophic flagellates in an ice-covered lake could account for up to 88% of the total observed uptake of bacteria-sized particles. As an extreme, in some high mountain lakes (Medina-Sá nchez et al 2004), and in some ponds during the cold seasons (Hitchman and Jones 2000), the entire measured bacterivory has been assigned to plastidic flagellates.…”
mentioning
confidence: 99%